Food practices of the first farmers of Europe: Combined use-wear and microbotanical studies of Early Neolithic grinding tools from the Paris Basin. (April 2021) - Hamon, Caroline; Cagnato, Clarissa; Emery-Barbier, Aline; Salavert, Aurélie
Highlights: Use-wear, starch grains and phytoliths analysis is powerful to highlight multifunctionality of grinding tools. In the Linearbandkeramik, processing of cereals and legumes is dominant. Tubers and rhizomes appear to have been regularly ground on querns. Different steps in plants processing are evident, such as dehusking, heating, and sprouting. Bark and ferns are transformed for their varied medicinal properties. Abstract: Food practices have always been a key issue to reconstruct part of the cultural identities of past and present societies. In archaeology, the question of vegetal processing and consumption has generally been discussed through different, yet complementary lenses that include botanical remains and cooking pots. However, it has seldom been integrated in a combined approach. Our paper explores the characteristics and role of plant transformation in Early Neolithic contexts from the Paris Basin (5100–4900 BCE), by combining use-wear analysis of grinding tools and the study of microbotanical remains (starch grains and phytoliths). Our integrated approach reinforces the interpretations and reduces the methodological limitations that arise when each analysis is considered separately. It also proposes a more complex vision than initially expected regarding the uses and lifecycles of grinding tools in daily plant preparation. Together with the dominant processing of cereals and legumes, tubers and rhizomes appear to have been regularly ground on querns. Different steps in plants processing are also evident, such as dehusking, heating, and sprouting. Other clues point towards the transformation of bark and ferns, known for their varied medicinal properties. These results and related methodological issues support discussions regarding the possible conservatism or innovations in vegetal food practices of Early Neolithic farmers inhabiting a region located at the most westerly point of the Linearbandkeramik expansion during the final centuries of this first wave of Neolithic dispersal throughout the European continent.